Assessment of Fasudil on Contrast-Associated Acute Kidney Injury Using Multiparametric Renal MRI - Wang, Bin; Wang, Yongfang; Tan, Yan; Guo, Jinxia; Chen, Haoyuan; Wu, Pu-Yeh; Wang, Xiaochun; Zhang, Hui (Frontiers in Pharmacology, 2022)
Aims: To evaluate the utility of fasudil in a rat model of contrast-associated acute kidney injury (CA-AKI) and explore its underlying mechanism through multiparametric renal magnetic resonance imaging (mpMRI). Methods: Experimental rats (N=72) were grouped as follows: controls (n=24), CA-AKI (n=24), or CA-AKI+Fasudil (n=24). All animals underwent two mpMRI studies (arterial spin labeling, T1 and T2 mapping) at baseline and post iopromide/fasudil injection (Days 1, 3, 7, and 13 respectively). Relative change in renal blood flow (ΔRBF), T1 (ΔT1) and T2 (ΔT2) values were assessed at specified time points. Serum levels of cystatin C (CysC) and interleukin-1β (IL-1β), and urinary neutrophil gelatinase-associated lipocalin (NGAL) concentrations were tested as laboratory biomarkers, in addition to examining renal histology and expression levels of various proteins (Rho-kinase [ROCK], α-smooth muscle actin [α-SMA]), hypoxia-inducible factor-1α (HIF-1α), and transforming growth factor-β1 (TGF-β1) that regulate renal fibrosis and hypoxia. Results: Compared with the control group, serum levels of CysC and IL-1β, and urinary NGAL concentrations were clearly increased from Day 1 to Day 13 in the CA-AKI group (all p<0.05). There were significant reductions in ΔT2 values on Days 1 and 3, and ΔT1 reductions were significantly more pronounced at all time points (Days 1-13) in the CA-AKI+Fasudil group (vs CA-AKI) (all p<0.05). Fasudil treatment lowered expression levels of ROCK1, and p-MYPT1/MYPT1 proteins induced by iopromide, decreasing TGF-β1 expression and suppressing both extracellular matrix accumulation and α-SMA expression relative to untreated status (all p<0.05). Fasudil also enhanced PHD2 transcription and inhibition of HIF-1α expression after CA-AKI. Conclusions: In the context of CA-AKI, fasudil appears to reduce renal hypoxia, fibrosis, and dysfunction by activating (Rho/ROCK) or inhibiting (TGF-β1, HIF-1α) certain signaling pathways and reducing α-SMA expression. Multiparametric MRI may be a viable noninvasive tool for monitoring CA-AKI pathophysiology during fasudil therapy.